Delimitation of homogeneous regions in the UNIFESP/EPM healthcare center coverage area based on sociodemographic indicators - Harada, Karina Yuri; Silva, Julieta Gonçalves; Schenkman, Simone; Hayama, Eliana Tiemi; Santos, Francisco Roberto Gonçalves; Prado, Mariângela Cainelli de Oliveira; Pontes, Regina Helena Petroni (São Paulo Medical Journal, 1999)
CONTEXT: The drawing up of adequate Public Health action planning to address the true needs of the population would increase the chances of effectiveness and decrease unnecessary expenses. OBJECTIVE: To identify homogeneous regions in the UNIFESP/EPM healthcare center (HCC) coverage area based on sociodemographic indicators and to relate them to causes of deaths in 1995. DESIGN: Secondary data analysis. SETTING: HCC coverage area; primary care. SAMPLE: Sociodemographic indicators were obtained from special tabulations of the Demographic Census of 1991. MAIN MEASURES: Proportion of children and elderly in the population; family providers’ education level (maximum: >15 years, minimum: <1 year) and income level (maximum: > 20 minimum wages, minimum: <1 minimum wage); proportional mortality distribution. RESULTS: The maximum income permitted the construction of four homogeneous regions, according to income ranking. Although the proportion of children and of elderly did not vary significantly among the regions, minimum income and education showed a statistically significant (p<0.05) difference between the first region (least affluent) and the others. A clear trend of increasing maximum education was observed across the regions. Mortality also differed in the first region, with deaths generated by possibly preventable infections. CONCLUSION: The inequalities observed may contribute to primary health prevention.